Taking sides : - Alexander, Alison (McGraw Hill, 2011)
This was a required book for a university-level class on mass media. To read the review, you'd think that the essays are presented in a pro-con format on any given issue, which in a sense, they are. However, many of the essays don't even address the topic that they are supposed to represent -- let alone hold a point of view on that topic. It almost seems as though the editors grabbed the nearest essay they could find that was even remotely relevant to the subject at hand.